Faktor-Faktor Yang Mempengaruhi Tingkat Kesabarandalam Menjalani pengobatan pada Pasien Diabetes Mellitus Di RSUD Chasbullah Abdulmadjid Kota Bekasi - Farozi .; Ummu Habibah (JURNAL KESEHATAN BHAKTI HUSADA, 2020)
Indonesia is ranked sixth with the higest number of people with Diabetes Mellitus after India, China,Japan and Brazil. Health Departemen Research results published in 2008 showed a prevalence of DMin Infonesia of 5,7% (around 12 million people) of Indonesia’s population suffering from DM and asmany as 70 % of the total population did not know that they have DM (Kariadi, 2009). The purpose ofthis study was to determine the factors that influence the level of patience of DM patients undergoingtreatment at Regional Public Hospital Chasbullah Abdulmajid of Bekasi2019. The research method isquantitative cross sectional eith sample collection techiques using simple random sampling. Thenumber of samples was 39 respondents. Data collection procedure is done by giving a questionnaireabout three items that describe the level of patience of respondents, namely self control in the facedisaster, strength in carrying out religious orders and the ability to refrain from religious prohibitions.The resulrs of the study using the chi square test found age, education, sex and history of DM arefactors that influence the level of patience of respondents with long history of DM has the higest pvalueof 0,000 (p-value< 0,05). It is hoped that the results of this study will be beneficial for hospitalservices in spiritual programs to support the recovery patients of DM.